Prevention of dengue fever in childhood: effects of participating in a championship with an educational game - do Nascimento, Aline Rosa; Borloti, Elizeu; Haydu, Verônica Bender (Perspectivas em Análise do Comportamento, 2018)
Contamination cases by the dengue virus are a major concern in Brazil. Studies upcoming from Behavior Analysis allow to establish strategies to teach behaviors to prevent the dengue fever. This study aimed to evaluate the effects of the participation of students in a championship with the board game Nossa Turma Contra a Dengue (which teaches prevention rules) on verbal and nonverbal behaviors of dengue prevention. Sixteen students participated in the championship. Before and after the board game, the participants carried out individually a Practical Evaluation Activity (preventive actions to control the proliferation of dengue), answered a questionnaire about the rules on the prevention of dengue fever, and played an adapted version of the game Tapa Certo®. Participants’ parents were interviewed before and after the championship, answering questions about dengue fever prevention behaviors presented by the participants at home. After the championship, 12 participants increased the score in the Practical Evaluation Activity and 15 of 16 participants don’t change the performance on the questionnaire. In the evaluation with the Tapa Certo®, there was an increase in the scores of participants who had not correctly answered all the questions at the Pre-Intervention Test. It is suggested that the participation on a championship was effective to promote behaviors on dengue fever’s prevention.